2022
DOI: 10.1002/adma.202200344
|View full text |Cite
|
Sign up to set email alerts
|

Progress and Future Prospects of Wide‐Bandgap Metal‐Compound‐Based Passivating Contacts for Silicon Solar Cells

Abstract: Figure 8. a) Dependence of work function on the energy gap of practical used TCO materials. b,c) Work function (○), carrier concentration (▫) and bandgap energy (Δ) as function of In 2 O 3 content for ZnO-In 2 O 3 film (b), SnO 2 content for In 2 O 3 -SnO 2 films (c). a-c) Reproduceded with permission. [91] Copyright 1998, Elsevier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 117 publications
(276 reference statements)
0
34
0
Order By: Relevance
“…Combining with low-WF metals, they can form excellent ihmic contacts with c-Si, making photogenerated electrons collected efficiently.Despite the successful demonstration of carrier selectivity, it is widely accepted that environmental and thermal stability remains one of the challenges for dopant-free contacts to be considered for industrial adoption. [20][21][22][23][24] A lot of dopant-free contacts are found to be sensitive to air exposure, especially when combined with heating, leading to the degradation of solar cell performance. [24][25][26][27][28][29] For example, ρ c of KF x /Al and CsF x /Al increase by more than one order of magnitude when exposed to air for 1000 h. [14] Furthermore, the V OC and FF of the c-Si solar cell using ZnO/LiF/Al as the electron-selective contact decrease from 727 mV and 78% to 428 mV and 46.5% within 75 h because of the interaction of ZnO/LiF/Al stack with air.…”
mentioning
confidence: 99%
“…Combining with low-WF metals, they can form excellent ihmic contacts with c-Si, making photogenerated electrons collected efficiently.Despite the successful demonstration of carrier selectivity, it is widely accepted that environmental and thermal stability remains one of the challenges for dopant-free contacts to be considered for industrial adoption. [20][21][22][23][24] A lot of dopant-free contacts are found to be sensitive to air exposure, especially when combined with heating, leading to the degradation of solar cell performance. [24][25][26][27][28][29] For example, ρ c of KF x /Al and CsF x /Al increase by more than one order of magnitude when exposed to air for 1000 h. [14] Furthermore, the V OC and FF of the c-Si solar cell using ZnO/LiF/Al as the electron-selective contact decrease from 727 mV and 78% to 428 mV and 46.5% within 75 h because of the interaction of ZnO/LiF/Al stack with air.…”
mentioning
confidence: 99%
“…We have shown that nanolayers, 1-3 nm in thickness, of PECVD SiNx and ALD AlOx can be fabricated and produce low resistivity tunnelling contacts below 100 mΩ·cm 2 . Similar dielectrics have also been investigated in both DFPC and poly-Si contact structures [10], [37], [44], [65] This section discusses other works reported as a comparison to the results presented in Section III. There are two main types of contact structures, dopant free passivating contacts and poly-Si contacts.…”
Section: Discussionmentioning
confidence: 99%
“…There are two main types of contact structures, dopant free passivating contacts and poly-Si contacts. DFPC structures have been reported with 𝜌 𝑐 typically between 30-200 mΩ·cm 2 [10]. The structures most commonly use metal oxides which have a negative valence band offset so thicker layers can be used and still maintain low contact resistivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations